EFEKTIVITAS MODUL DIGITAL BERBASIS E-LEARNING PADA MATAKULIAH PENDIDIKAN KARAKTER DI STKIP MUHAMMADIYAH MUARA BUNGO - Muhammad Hakiki; Arisman Sabir; Ana Maryana (Jurnal Muara Pendidikan, 2022)
The very rapid development of science and technology in the Industrial Revolution Era 4.0 also had an impact on the world of education, where the increasing use of information technology in the world of education, as well as the occurrence of the covid 19 pandemic which resulted in face-to-face learning processes could not be carried out directly, so that the learning process in Networking (Online) must do. The online learning that was carried out experienced many obstacles, one of which was the absence of a digital module that was specifically designed for online learning. So it is necessary to develop a digital module based on e-learning. The purpose of this research is to produce digital modules that can be used in the learning process through E-learning. This research is a research and development research and development (R&D). The development model used in this study is a 4-D model (Four D-Model), which consists of 4 main stages, namely, Define, Design, Develop and Disseminate. The research subjects were all students of the Information Technology Education Study Program (PTI) in the second semester even at STKIP Muhammadiyah Muara Bungo in 2021/2022. The sampling technique used is total sampling. Based on the results of the pretest and posttest data analysis at a significance level of 0.05, the normality value of the pretest data was 0.163 which can be seen in the asymp sig (2-tailed). Because the normality value is greater than the significance value (0.163>0.05), the data is declared to be normally distributed. Furthermore, the posttest value obtained data normality value of 0.090 which can be seen in the asymp sig (2-tailed), because the normality value is greater than the significance value (0.090> 0.05) then the data is declared normally distributed. 0.000 (0.000 <0.05) means that there is a significant difference in student learning outcomes before and after using the learning module through e-learning. Then if t-count <t-table, then there is an increase in learning outcomes after using the learning module through e-learning. Vice versa, if t-count>t-table, then there is no increase in learning outcomes after using the learning module through e-learning. table (-15,453<2,019) it is stated that there is an increase in learning outcomes between before and after the implementation of the learning module through e-learning.